An adult face bias in infants that is modulated by face race. (September 2017) - Heron-Delaney, Michelle; Damon, Fabrice; Quinn, Paul C.; Méary, David; Xiao, Naiqi G.; Lee, Kang; Pascalis, Olivier
The visual preferences of infants for adult versus infant faces were investigated. Caucasian 3.5- and 6-month-olds were presented with Caucasian adult vs. infant face pairs and Asian adult vs. infant face pairs, in both upright and inverted orientations. Both age groups showed a visual preference for upright adult over infant faces when the faces were Caucasian, but not when they were Asian. The preference is unlikely to have arisen because of low-level perceptual features because: (1) no preference was observed for the inverted stimuli, (2) no differences were observed in adult similarity ratings of the upright infant–adult face pairs from the two races, and (3) no differences between the infant and adult faces were observed across races in an image-based analysis of salience. The findings are discussed in terms of the social attributes of faces that are learned from experience and what this implies for developmental accounts of a recognition advantage for adult faces in particular and models of face processing more generally.